ANALISIS FAKTOR KEMAMPUAN BAHASA VERBAL PADA ANAK USIA 5-6 TAHUN DI TK NEGERI KELAPA LIMA - Febrianti Bhau Bai, Maria; Margiani, Kristin; Paulin Nalle, Andriani; Yuniati, Yohana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and describe the factors that influence the verbal language skills of children aged 5-6 years at TK Negeri Kelapa Lima, Kupang, East Nusa Tenggara. A qualitative case-study approach was employed, involving three children whose verbal language development had not yet reached its optimal level. Data were collected through observations, in-depth interviews with teachers and parents, as well as documentation. The data were then analyzed using data reduction, data display, and conclusion drawing/verification, accompanied by source triangulation. The findings reveal that verbal language skills are influenced by a combination of internal and external factors. Internal factors include genetic history, linguistic intelligence, and gender, while external factors encompass parenting styles, the intensity of parent-child communication, birth order, and the surrounding environment. The three subjects exhibited different dominant causes: parent-child communication patterns for the first child, social environment and shyness for the second child, and the quality of the language models received at home for the third child. Overall, external factors, particularly parental communication styles and environmental stimulation, were found to be more decisive than internal factors in shaping children's verbal language development. These findings underscore the importance of consistent and responsive language stimulation from parents, teachers, and the surrounding environment to optimize early childhood verbal language skills.